1993
DOI: 10.1111/j.1476-5381.1993.tb13979.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual contractile effects of ATP released by field stimulation revealed by effects of α,β‐methylene ATP and suramin in rat tail artery

Abstract: 1 The field stimulation-induced release of endogenous ATP and noradrenaline (NA) and contractile response in rat isolated tail artery were examined. The release of ATP was studied by extracellular electrophysiological recording and that of NA by a novel voltammetrical technique. The effects of the P2-purinceptor antagonist, suramin, on these parameters were compared with those of a,-methylene ATP, a P2x-purinoceptor desensitizing agent. 2 Neither a,-methylene ATP (101 M) nor suramin (100-500I1M) had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
5
35
0
Order By: Relevance
“…This range of expression of P2X receptors may explain in part the differences in the magnitude of P2X receptor-mediated responses between different arteries, as substantial P2X receptor-mediated neurogenic vasoconstriction is most commonly seen in small and medium arteries [9, 11, 55, 56]. In larger arteries, the P2X receptor-mediated neurogenic component is usually small [10, 11]. This pattern is consistent with the relatively lower innervation density in larger arteries [57]and indicates that there is a correlation between the level of innervation, P2X receptor expression and functional responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This range of expression of P2X receptors may explain in part the differences in the magnitude of P2X receptor-mediated responses between different arteries, as substantial P2X receptor-mediated neurogenic vasoconstriction is most commonly seen in small and medium arteries [9, 11, 55, 56]. In larger arteries, the P2X receptor-mediated neurogenic component is usually small [10, 11]. This pattern is consistent with the relatively lower innervation density in larger arteries [57]and indicates that there is a correlation between the level of innervation, P2X receptor expression and functional responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…9 and 10], (2) the diameter of the artery [11]and (3) the parameters of stimulation [12, 13]. For example, in small arterioles, the response to sympathetic nerve stimulation is mediated solely by P2X receptors [9], whereas in the large caudal (tail) artery, the adrenergic component dominates [10]. One possibility is that the range of responses may reflect an heterogeneity in the P2X receptor populations or density expressed by different arteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EJPs were later shown to be due to ATP released as a cotransmitter from sympathetic nerves, because they were blocked by desensitization of P2X receptors by a,b-meATP (Sneddon and Burnstock, 1984b;Neild and Kotecha, 1986). Suramin, a P2 receptor antagonist, was also shown to block the ATP component of sympathetic neurotransmission of the rat tail artery (Bao and Stjärne, 1993). Coreleased NA and ATP from sympathetic nerves supplying the rail artery have synergistic postjunctional contractile actions on the smooth muscle (Johnson et al, 2001;Johnson, 2010).…”
Section: B Rat Tail Arterymentioning
confidence: 99%
“…PRA in group I was higher than in group H 123P (251'5 ± 31'6 vs. 78'0 ± 6'2 ngAI ml-1 h -t, P < 0'01), and both were elevated compared with the Cont group (2'8 ± 0'3 ngAI ml-1 h- In vitro studies have indicated that the nature of neuroeffector transmission is influenced by the pattern of sympathetic discharges. Synchronous and asynchronous models of sympathetic activity have been used to study neuroeffector transmission in the caudal ventral artery (CV A) of the rat in vitro using either electrical stimulation (synchronous, Bao & Stjarne, 1993) or ciguatoxin (asynchronous, Brock et al 1997). Using a focal recording technique, we have previously shown in vivo that the discharges of single sympathetic postganglionic neurones (PGNs) innervating the CV A are rhythmical (dominant rhythm: T-rhythm, Johnson & Gilbey, 1996).…”
Section: Bi52ttmentioning
confidence: 99%